Martensitic Transformation Characteristic of Ni-Mn Based Ferromagnetic Shape Memory Alloys - Ajit Behera; Asit Behera; S.C. Mishra (Institute of Advanced Engineering and Science, 2013)
Ferromagnetic shape memory alloys emerge as new functional materials which have interesting magnetomechanical coupling effects such as the ferromagnetic shape memory effect. These types of materials significantly change their shape and dimensions under the application of external fields i.e. either by using thermal energy or magnetic energy. Among them, some are the magnetostrictive alloys which in turn can change their shape by magnetic field up to 0.1 percent and by mechanical stress up to 10 percent in martensitic state. Up to 6 percent deformation can be obtained in materials under the action of the magnetic field which undergo the thermoelastic transformation into ferromagnetic phase. Due to higher processing cost and costly elements for alloying, ferromagnetic shape memory alloy have not so broadly utilization and satisfactorily use. Among different type of Ni-Mn based Heusler ferromagnetic shape memory alloys, Ni-Mn-Sn alloy have potential properties and exhibits lower cost. In this paper martensitic transformation of Ni50Mn50-ySny (y= 5, 10, 12.5) alloys were investigated. By differential scanning calorimetric measurement, it has been observed that, by keeping one element i.e. Ni as constant weight percentage, if we increase the weight percent of Sn; then martensitic starting temperature as well as austenitic starting temperature gradually decreases.